Milly, Molly and Melonkey - Pittar, Gill; Morrell, Cris (MM House Pub. Gisborne, N.Z., 2003)
Milly and Molly try and help their friend Melonkey by finding out what happiness is. Includes teaching guide. Suggested level: junior